A comparison study on the natural and half-soaking galvanic accelerated corrosion of reinforced concrete based on an improved electrochemical model. (20th November 2020) - Tian, Ye; Zhang, Guoyi; Jin, Xianyu; Jin, Nanguo; Ye, Hailong; Yan, Dongming; Tian, Zushi
Highlights: An improved electrochemical model which can be applied to analyze both the natural corrosion and galvanic accelerated corrosion. An objective and comparative research on natural corrosion and galvanic accelerated corrosion. Self-balance of macrocell and microcell corrosions. Abstract: In order to investigate the half-soaking galvanic accelerated corrosion and natural corrosion comparatively, an improved electrochemical model was established. Taking the diffusion of ions, potential distribution and polarization into consideration, the difference between two corrosion methods were essentially revealed. By changing the boundary conditions of the model, Finite Element Method (FEM) was applied to simulate corrosion potential distribution, ions concentration and current density both on the steel–concrete interface and within concrete. In natural corrosion, macrocell corrosion was coupled with microcell corrosion, and the anodic and cathodic current densities were self-balanced. To model the real corrosion under natural environment, the cathodic to anodic area ratio ( A c / A a ) of macrocell was assumed to be changing with the development of corrosion. In galvanic accelerated corrosion, the influence of external ions concentration on current density was considered, which eventually affected the distribution of rust layer of steel rebar. The simulation results agree well with the test data collected from literatures. A further discussion indicates that impressed current density significantly affects the time ratio of natural corrosion to galvanic accelerated corrosion, while the NaCl solution concentration shows no clear influence on time ratio. The bearing capacities of the corroded steel rebar under half-soaking method (HSM) and natural corrosion will show no clear difference, but the HSM method is not very appropriate for studying the corrosion cracking process of reinforced concrete.